Digital Marketing Strategy in Increasing Visitor Traffic at Etern Street Coffee - Setiadi, Mochamad Bilal; Oktario, Muhammad Beno; Imawan, Khaerudin (Asian Journal of Management Analytics, 2025)
The advancement of digital technology has significantly impacted the transformation of marketing strategies, particularly within the culinary business sector. This study aims to evaluate the implementation of digital marketing strategies employed by Kedai Etern Street Coffee through the use of social media platforms such as Instagram and TikTok, with the main objective to increase customer visits and fostering customer loyalty. A descriptive qualitative method was employed, utilizing in-depth interviews, field observations, and documentation for data collection. Theoretically, this research is grounded in the concept of digital marketing communication. The findings reveal that the use of creative content, active engagement with customers, and collaboration with influencers play a crucial role in enhancing the appeal of Kedai Etern Street Coffee. Additionally, the utilization of analytics to understand customer preferences supports the optimization of their marketing strategies. An integrated and adaptive digital marketing strategy has proven to significantly enhance the competitiveness of Kedai Etern Street Coffee in the era of technology-driven marketing.